Respuesta :

Answer:

3x + 2y + 12 = 0

Step-by-step explanation:

1) Rewrite 2x - 3y = 6 as 2x - 6 = 3y.  Then we know the slope of the desired line is (2/3).

2) Take the negative reciprocal of this, obtaining -3/2.  This is the slope of any line which is perpendicular to 2x - 6 = 3y.

3) Use the slope-intercept form of the equation of a line, y = mx + b:

Replace y with -3, x with -2, and m with -3/2:

-3 = (-3/2)(-2) + b, or

-3 = 3 + b.  Thus, b = -6, and the desired equation is y = (-3/2)x - 6, or

2y = -3x - 12, or

3x + 2y + 12 = 0